Upwelling processes driven by contributions from wind and current in the Southwest East Sea (Japan Sea) - Kim, Deoksu; Choi, Jang-Geun; Park, Jinku; Kwon, Jae-Il; Kim, Myeong-Hyeon; Jo, Young-Heon (Frontiers in Marine Science, 2023)
The occurrence of coastal upwelling is influenced by the intensity and duration of sea surface wind stress and geophysical components such as vertical stratification, bottom topography, and the entrainment of water masses. In addition, strong alongshore currents can drive upwelling. Accordingly, this study analyzes how wind stress and ocean currents contribute to changing coastal upwelling along the southwest coast of the East Sea (Japan Sea), which has not yet been reported quantitatively. This study aims to estimate each geophysical factor affecting upwelling processes using the Upwelling Age index. The index assesses the major contributors to the upwelling process using the relationship between physical forcing and upwelling water fraction estimated from shipboard hydrographic data from January 1993 to October 2018. These findings reveal that wind-driven upwelling was dominant off the northern coast. In contrast, current-driven upwelling prevailed off the southern coast. These results suggest that persistent alongshore currents through the Korea Strait make the southern region a prolific upwelling area. Accordingly, it can shed light on the mechanisms of coastal upwelling in the study area, which is crucial for understanding the influence of physical forces on ocean ecosystems.